Cognitive appraisals and lived experiences during injury rehabilitation: A narrative account within personal and situational backdrop - Roy, J.; Mokhtar, A.H.; Karim, S.A.; Mohanan, S.A. (Tehran University of Medical Sciences, 2015)
Background: The article highlights an athlete’s cognitive appraisals form the onset to return to play. The narrative provides how an athlete constructs a sense of self within personal and situational factors and describes the subjective experiences during rehabilitation